Optimization of MEMS piezo-electric sensor for smart textile application / Muhammad Hassan Rehman - Muhammad Hassan, Rehman (2018)
MEMS piezoelectric cantilever based sensor for smart textile application are useful to monitoring a various physiological parameter. Especially blood pressure necessary to measure which treat critical conditions like hypotension and hypertension and it can cause heart failures and attacks, strokes, dizziness and shock. Blood pressure is measured in millimeter of mercury(mmHg) units. During each heart beat blood pressure varies between systolic (maximum) and diastolic (minimum). Hence direct measure of heart beat can be considered as the determination of the blood pressure. Normal human systolic pressure is 120mmHg and diastolic pressure is 80mmHg. For blood pressure monitoring application, health care industry combines smart shirt with compatible sensors which are required to operate in the range of 50mmHg-180mmHg. MEMS piezoelectric cantilever based sensors are widely in blood pressure measurement because it provides higher sensitivity to pressure, tunable sensitivity, simple structure and micro in size. In this research project, a U-shaped MEMS piezoelectric cantilever based sensor is designed and demonstrated using COMSOL Multiphysics software. Result obtained from the simulation is the deflection of the U-shaped cantilever when normal diastolic pressure 80mmHg is applied. Among other piezoelectric material Lead Zirconate Titanate (PZT-5H) as a sensing layer of U-shaped cantilever gives better sensitivity at diastolic condition (80mmHg) showing displacement and electric potential of 11.456μm and 2.0523V which is 41.40 higher than rectangle shaped cantilever. For the conclusion, a piezoelectric MEMS cantilever based sensor is successfully designed, simulated and optimized. Optimization parameter had also been performed at different length of cantilever which shows that longer gives greater deflection at diastolic condition and improves the sensitivity of sensor due to the uniform distribution of stress throughout the surface of cantilever. While by using U-shaped of cantilever the size of the cantilever reduces and gives better performance as compare to rectangle shaped cantilever.